Chitosan magnetic nanocomposites for gene delivery - Vannessa, Lawai; Zainab, Ngaini (Woodhead Publishing, 2021)
The application of magnetic nanoparticles coated with cationic polymers in the biomedicine field has been studied extensively. The biological properties of chitosan and magnetic nanoparticles such as biocompatibility, biodegradability, and targeted delivery make nanocomposites an excellent choice in gene delivery systems. Several methods of preparing nanocomposites have been reported (i.e., microemulsion, thermal decomposition, solvothermal), which mostly are expensive and tedious methods. The coprecipitation method is widely employed and able to produce uniform and small particle sizes, which are highly suitable for gene delivery. The high transfection efficiency of chitosan magnetic nanocomposite was tested in vitro and in vivo against cancerous cells (B16F10 murine melanoma cells, SF767 human glioblastoma) and normal cells (HEK-293T). In vivo magnetofection study indicated the efficiency and applicability of chitosan magnetic nanocomposites for gene delivery.